Shota Rustaveli’s “The Man in the Panther Skin” in German Schools - Steffi Chotiwary-Jünger (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2011)
German and Georgian Kartvelologists have hitherto not been aware of the fact that the Georgian author Rustaveli and his poem “The Man in the Panther Skin” entered a German school textbook. There is no reference to this book in the last German Bibliography (Georgia -the German-language world, 2008), though the said textbook was issued in 1985 and was used in schools of the German Democratic Republic. At the time, Rustaveli was almost unknown in the German Federal Republic. Following the unification of Germany Rustaveli was not entered in any textbook.